2005
DOI: 10.1248/bpb.28.902
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodic Activity of Fractions and Cynaropicrin from Cynara scolymus on Guinea-Pig Ileum

Abstract: Cynara scolymus (Compositae), popularly known as "alcachofra" or "artichoke", is widely cultivated In Mediterranean and American countries, and its sprout is commonly eaten as a vegetable. Its leaves are frequently used in folk medicine in many countries, to treat several ailments, including hepatitis, hyperlipidemia, and obesity, dyspeptic disorder, among others. Clinical and pre-clinical trials have confirmed the therapeutic potential of this plant, particularly in the treatment of hepato-biliary dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 14 publications
1
27
0
3
Order By: Relevance
“…In addition, after successive washings, the contractile response to agonists was restored. These findings are consistent with the popular use of artichoke as a home remedy for the treatment of gastrointestinal disturbances (Emendörfer et al, 2005). In the same context, another recent study showed that cynaropicrin has a weak in vitro acetyl cholinesterase inhibition with an IC 50 value of 10 μg/ml and radical scavenging activity against 1,1-diphenyl-2-picryl-hydrazil (DPPH) radicals (Hegazy et al, 2016).…”
Section: Gastric Actionssupporting
confidence: 90%
“…In addition, after successive washings, the contractile response to agonists was restored. These findings are consistent with the popular use of artichoke as a home remedy for the treatment of gastrointestinal disturbances (Emendörfer et al, 2005). In the same context, another recent study showed that cynaropicrin has a weak in vitro acetyl cholinesterase inhibition with an IC 50 value of 10 μg/ml and radical scavenging activity against 1,1-diphenyl-2-picryl-hydrazil (DPPH) radicals (Hegazy et al, 2016).…”
Section: Gastric Actionssupporting
confidence: 90%
“…The dichloromethane fraction showed the most promising biological effects, with an IC 50 of 0.93 (0.49-1.77) lg/mL. Its main active component, the sesquiterpene lactone cynaropicrin, exhibited potent activity, with IC 50 of 0.065 (0.049-0.086) lg/mL, being about 14-fold more active than dichloromethane fraction and having similar potency to that of papaverine, a well-known antispasmodic agent (Emendoerfer et al, 2005).…”
Section: Other Activitiesmentioning
confidence: 99%
“…It has recently been shown that cynaropicrin (Fig. 1) has an antispasmodic activity [21], is a potent, irreversible inhibitor of the bacterial enzyme MurA [22], may participate in inflammatory response by inhibiting the production of inflammatory mediators and the proliferation of lymphocytes [23], shows significant cytotoxicity against five cultured human tumour cell lines [24] and may be a potential anticancer agent against some leukocyte cancer cells such as lymphoma or leukaemia [25]. It is desirable to remove the bitter compounds selectively from the leaves of L. carthamoides, as the extract could be used in the food industry and in the animal production as an additive to feedstuff to improve the digestion of monogastric animals and galliformes, while the ecdysteroids would be extracted from the leaves in the next step by an organic solvent.…”
Section: Introductionmentioning
confidence: 99%